Analisis Pembangunan Bendungan Bener Dalam Perspektif Hak Menguasai Negara Studi Kasus Putusan Nomor : 68/G/PU/21/PTUN.SMG - Putri Inayah; Amanda Kirani Fauzi; Immanuela Yvette Aveyory (Peneliti.net, 2023)
The development of national strategic projects during the era of President Joko Widodo was carried out intensively. This project was initiated with the aim of improving people's welfare. In every development, land is definitely needed. However, state land is already very scarce and even depleted. Therefore, the state uses people's land by way of land acquisition. However, land acquisition carried out by the government often differs from the procedures that have been implemented. Often, development that should bring prosperity to the people actually harms the people.